2003
DOI: 10.1039/b211836j
|View full text |Cite
|
Sign up to set email alerts
|

Dispersing palladium nanoparticles using a water-in-oil microemulsion—homogenization of heterogeneous catalysis

Abstract: Palladium nanoparticles dispersed by a water-in-oil microemulsion are very effective catalysts for hydrogenation of olefins in an organic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 12 publications
2
44
0
3
Order By: Relevance
“…2 nm [38]. The intricated problem of equilibrium between Pd(0) as colloidal nanoparticles and Pd(0) or Pd(II) as monomolecular soluble forms was also discussed for carbonylation [39,40] and hydrogenation using water-in-oil-microemulsion [41].…”
Section: Introductionmentioning
confidence: 99%
“…2 nm [38]. The intricated problem of equilibrium between Pd(0) as colloidal nanoparticles and Pd(0) or Pd(II) as monomolecular soluble forms was also discussed for carbonylation [39,40] and hydrogenation using water-in-oil-microemulsion [41].…”
Section: Introductionmentioning
confidence: 99%
“…ME-derived nanoparticles are widely used in catalytic reactions, mainly as a nanoparticle-containing MEs per se or deposited onto supports. The use of ME itself [18][19][20][21][22][23][24][25] implies the addition of extra components to the catalytic reaction mixture (hydrocarbon, water, surfactant, excess of a metal re-ducing agent). This leads to an increase of the reaction volume, and a catalytic reaction may be affected through "medium" and "solubilization" effects [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also reported the dispersion of palladium nanoparticles in a water/AOT/n-hexane microemulsion by hydrogen gas reduction of PdCl 4 2-and its efficiency for hydrogenation of alkenes in organic solvents [79]. UV-visible spectroscopy and TEM analysis revealed the formation of Pd nanoparticles with diameters in the range of 4 to 10 nm.…”
Section: Supercritical Microemulsions Used As Templates For the Stabimentioning
confidence: 84%
“…(Reprinted with the permission of the American Chemical Society[79]) Molar ratio of alkene/AOT/Na 2 PdCl 4 = 1/1/0.01 and 10 mL of n-hexane used as solvent (W = 15) at 30 8C. b) 1.7 mg Pd/C (0.17 mg or 1.6 lmol Pd) in 10 mL n-hexane.…”
mentioning
confidence: 99%